Many-body Quantum Reaction Dynamics near the Fusion Barrier - Dasgupta M. (EPJ Web of Conferences, 2014)
The understanding of quantum effects in determining nuclear reaction outcomes is evolving as improved experimental techniques reveal new facets of interaction dynamics. Whilst the phenomenon of coupling-enhanced quantum tunnelling is understood to arise due to quantum superposition, the observed inhibition of fusion at energies well below the barrier is not yet quantitatively understood. Collisions involving weakly-bound nuclei, which have low energy thresholds against breakup, present further challenges. Recent coincidence measurements for reactions of weakly bound stable nuclei have not only provided a complete picture of the physical mechanisms triggering breakup, but have also shown how information on reaction dynamics occurring on time-scales of ~zepto-seconds can be obtained experimentally. These new experimental findings demand major developments in quantum models of near-barrier nuclear reactions.